A Scoring System for Anterior Longitudinal Ligament Ossification of the Lumbar Spine in Diffuse Idiopathic Skeletal Hyperostosis: Relationship Between the Extent of Ligament Ossification and the Range of Motion. Issue 2 (March 2023) - Murakami, Yusuke; Morino, Tadao; Hino, Masayuki; Misaki, Hiroshi; Imai, Hiroshi; Miura, Hiromasa
Study Design: Retrospective observational study. Objective: To investigate the relationship between the extent of ligament ossification and the range of motion (ROM) of the lumbar spine and develop a new scoring system. Methods: Forty-three patients (30 men and 13 women) with lumbar spinal canal stenosis who underwent decompression from January to December 2018. Ligament ossification at L1/2 to L5/S was assessed on plain X-ray (Xp) and computed tomography (CT) using a modified Mata scoring system (0 point: no ossification, 1 point: ossification of less than half of the intervertebral disc height, 2 points: ossification of half or more of the intervertebral disc height, 3 points: complete bridging), and the intra-rater and inter-rater reliability of the scoring was assessed. The relationship of the scores with postoperative lumbar ROM was investigated. Result: Intra-rater reliability was high (Cronbach's α was 0.74 for L5/S on Xp but 0.8 or above for other sections), as was inter-rater reliability (Cronbach's α was 0.8 or above for all the segments). ROM significantly decreased as the score increased (scores 1 to 2, and 2 to 3). A significant moderate negative correlation was found between the sum of the scores at L1/2-L5/S and the ROM at L1-S (ρ = − 0.4493, P = 0.025). Conclusion: Our scoring system reflects lumbar mobility and is reproducible. It is effective for assessing DISH in fractures and spinal conditions, and monitoring effects on treatment outcomes and changes over time.